Pemasaran Produk Jamur Krispi Memanfaatkan Media Online di LKSA Yayasan Budi Mulia Bangunrejo Plosoklaten - Alvina Febriana Munfatikha (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
In the research that we conducted at LKSA Budi Mulia, of course there are also obstacles that must be resolved, therefore this research is also very helpful in solving these problems. The problem is about the marketing of MSME products in LKSA, where the marketing is still not reachable by the wider community. So that researchers will solve it by marketing these products using online media. With the media that is currently widely used, namely fb, ig, and wa. Before doing the marketing, there are several things we do, namely knowing how to cultivate it up to the harvesting process. Because this research only focuses on marketing. This research, of course, also has a good impact on LKSAs, including, to build an entrepreneurial spirit for the administrators, children, and the community around LKSA Budi Mulia, and also to increase LKSA's income for the sake of their welfare.